2022
DOI: 10.1002/ptr.7364
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Silymarin on the features of cardiometabolic syndrome in adults: A systematic review and meta‐analysis

Abstract: Some medicinal herbs and their effective components showed positive effects on the features of the cardiometabolic syndrome (CMS). The aim of the present systematic review and meta-analysis is to examine the effects of silymarin on the components of CMS in adults. Four electronic databases including PubMed/Medline, Scopus, Web of Science, and Embase were systematically searched up to December 31, 2020 to identify all eligible clinical trials. A random-effect model using DerSimonian and Laird method was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Using an established LC–MS analysis protocol, the SMEE prepared and investigated in the present study was found to be rich in silydianin and silychristin (51.2%), whereas silybin was found to be present in a much lower amount (<10%). It is worth mentioning that all published studies on S. marianum extracts have been focusing on silymarin that is rich in silybin (50%). ,,, , Our findings may hint at yet unexplored effects of silydianin and silychristin, and therefore, more research should be concentrated on these understudied flavonolignans.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Using an established LC–MS analysis protocol, the SMEE prepared and investigated in the present study was found to be rich in silydianin and silychristin (51.2%), whereas silybin was found to be present in a much lower amount (<10%). It is worth mentioning that all published studies on S. marianum extracts have been focusing on silymarin that is rich in silybin (50%). ,,, , Our findings may hint at yet unexplored effects of silydianin and silychristin, and therefore, more research should be concentrated on these understudied flavonolignans.…”
Section: Discussionmentioning
confidence: 79%
“…Silymarin, the main extract of S. marianum , has been extensively investigated in the literature as documented in recent reviews. However, these studies mainly focused on silybin, the main component of silymarin, ignoring the effect of other constituents . Additionally, the composition of silymarin is often unknown and can vary to a certain extent depending on the chemovariety of the plant, climatic conditions during plant growth, and processing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the SILY group, the liver histology was normal, with a clear typical lobular structure and a single layer of hepatocytes around the central vein. Based on previous literature [57][58][59][60][61] and the H&E results of the liver tissues of AALI mice, SILY has been conrmed to affect the blood ow by remitting hepatic lipid accumulation. Meanwhile, these results suggest that the improvement of AALI by pharmacological intervention can be visualized by NIR-II imaging of NTPB-NPs.…”
Section: Biocompatibility Of Ntpb-nps In Vivomentioning
confidence: 99%
“…Specifically, SIL can inhibit the generation of inflammatory agents from the liver, which play a significant role in the development of CVDs [11,39]. Several systematic reviews and meta-analyses have documented the positive impact of SIL on metabolic status [26], type 2 diabetes mellitus (T2DM) [24,40], and the features of CMS in adults [9,41]. However, the impact of SIL supplements on cardiovascular health in various consumer or patient groups has not been thoroughly evaluated, and the results are inconclusive, contradictory, and inconsistent.…”
Section: Introductionmentioning
confidence: 99%